The formation of economic and marketing prospects for the development of the market of information services - Pererva, P. G.; Nazarenko, Stanislav; Maistro, Ruslana; Danko, Taras; Doronina, Maya; Sokolova, Liudmyla (Технологічний центр, 2021)
This paper examines the current state and prospects of the European IT services market. A detailed analysis of economic indicators of the IT market in Europe. The marketing characteristics of the external market of IT services, in the formation of which the leading role belongs to export deliveries, are considered. It is established that the capacity of the international segment of the IT services market in most European countries is growing by an average of 20% annually, and the share of IT exports in the total structure of exports exceeds 8%. The forecast of changes in the domestic market of IT technologies in the post-Soviet countries is analyzed. According to the results, it was concluded that in the future the capacity of the domestic market of IT services may increase in 2024, in particular in Ukraine, to exceed $ 2 billion. The results of the study of the level of prices for IT services in the post-Soviet countries show that they mostly correspond to the prices for similar services in different groups of European countries (with different financial capabilities).

У даній роботі досліджується сучасний стан та перспективи розвитку європейського ринку ІТ-послуг. Проведено детальний аналіз економічних показників ринку ІТ в країнах Європи. Розглянуто маркетингові характеристики зовнішнього ринку ІТ-послуг, у формуванні якого провідна роль належить експортним поставкам. Встановлено, що місткість міжнародного сегмента ринку ІТ-послуг у більшості європейських країн щорічно зростає в середньому на 20 %, а частка експорту ІТ-технологій у загальній структурі експорту перевищує 8 %. Проаналізовано прогноз змін на внутрішньому ринку ІТ-технологій у пострадянських країнах. За результатами було зроблено висновок, що в майбутньому ємність вітчизняного ринку ІТ-послуг може зрости і в 2024 році, зокрема в Україні, перевищить 2 млрд доларів. Результати вивчення рівня цін на ІТ-послуги в пострадянських країнах свідчать про те, що вони переважно відповідають цінам на подібні послуги в різних групах європейських країн (з різними матеріальними можливостями).
Формування економічних і маркетингових перспектив розвитку ринку інформаційних послуг
Keywords: marketing research; IT services market; development indicators; market capacity; economic characteristics; маркетингові дослідження; ринок ІТ-послуг; показники розвитку; місткість ринку; економічні характеристики